Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan (Studi Kasus 5 Kabupaten/Kota di Provinsi Kalimantan Selatan) - Sari, Erlin Puspita; Saleh , Muhammad (PPJP ULM, 2024)
The study aims to see the effect of economic growth variables, human development index (HDI) and open unemployment rate partially and simultaneously on the poverty rate in 5 districts / cities of South Kalimantan Province in 2013-2022. This research uses the panel data regression calculation method with the help of the Eviews 12 application. The scope of this research takes 5 districts / cities in South Kalimantan Province, namely Tanah Bumbu,, Tapin, Hulu Sungai Selatan, Hulu Sungai Tengah and Banjarmasin City. The results of this study: (1) Economic Growth has a positive and insignificant effect. (2) Human Development Index has a negative and significant effect. (3) Open Unemployment Rate has a positive and significant effect. (4) Simultaneously, the variables of Economic Growth, Human Development Index and Open Unemployment Rate affect the Poverty Rate in 5 Regency / City of South Kalimantan Province in 2013-2022.